Penyuluhan Memberikan pelatihan senam kaki pada pasien DM di PKM Tarogong Kecamatan Tarogong Kidul Kabupaten Garut - Devi Ratnasari; Zahara Farhan; Hasbi Taobah Ramdani; Elang Mohamad Atoilah (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
Diabetes Mellitus is a disease that can be called the silent killer. Facts show that only about 50% of those diagnosed and realized they have diabetes. Sports activities such as diabetes foot exercise are one of the pillars of diabetes mellitus management. The method used in the activity is to carry out counseling using slides with material related to counseling and provide foot exercise training for DM patients, delivery of material, health checks, and questions and answers to provide opportunities for participants to ask certain things that are considered not yet clear and to evaluate participants' understanding of the material provided. This activity was attended by 20 participants who indicated diabetes mellitus. The results obtained from this activity by carrying out routine foot exercise training with a duration of 1 (one) week 3 (three) and maintaining a diet for people with diabetes mellitus can maintain normal sugar levels in the body so that it can be concluded that thereis an increase in knowledge and skills of people with Diabetes Mellitus. in preventing diabetic ulcers on the feet so that they can independently carry out foot exercises without any help from others.